Pengembangan Media Pembelajaran Kincir Angin Berbasis Stem Untuk Meningkatkan Keterampilan Mengomunikasikan Siswa Inklusi Kelas 4 Sekolah Dasar - Ida Sri Astutik (Jurnal Didaktika Pendidikan Dasar, 2020)
The purpose of this study is to develop SEM learning media based on SEM (Science, Technology, Engineering and Mathematics), improve communication skills, and find out the effectiveness of using STEM-based windmill learning media in the learning of students with special needs or the inclusion of 4th grade elementary school, because they have different characteristics with other children. Therefore we need a special educational institution so that their abilities can be honed to the maximum. The ability to communicate with 4th-grade inclusion students in primary schools has not been able to be maximized, this can be known from the average value obtained which is only 66.67. Homework that must be completed immediately and find a solution. So far, educators only use the lecture method and do not involve student activities in the classroom so students are not interested in learning activities. After using the STEM-based learning media, an increase in students' ability to communicate. The results show the average value increased by 19.04 significantly. The previous average value of 66.67 became 85.71. During the learning process, it was concluded that the use of STEM-based learning media for windmills could improve the communication skills of 4th-grade inclusion students in elementary schools.